Violencia de género en la música del discurso en la letra de las canciones del reggaetón - Cadena Ruiz, Daniela Estefani (2020)
In addition to being a harmonious sound system, the art of music is characterized by the ability to make expressive and comunicative manifestations. This research reflects on the role that music plays as an alternative means of communication and as a socio-cultural phenomenon that suggests ways of seeing and understanding the world. In addition, one of the most representative genres of Latin music was analyzed, which is currently the genre of reggaeton, which takes force from the year 2000. However, this urban musical genre triggers empty messages and out of respect, especially when it is about women, presenting violent messages and influencing to the ideology of those who listen to it. A discourse analysis was applied both as a qualitative methodological contribution and as part of the theoretical framework. Through two different approaches: social and gender. Likewise, the methodological approach is based on four reggaeton songs that were trending in 2019, in two of the most listened radio stations in Latacunga city, Cotopaxi province in Ecuador. The discourse analysis helps to identify discrimination against women because of the influence of the reggaeton musical genre in origin of their musical lyrics. Violence and stereotypes towards women are evident not only in real life, but have also been integrated into the various media through music and advertising; It should be noted that it has increased in recent years in an almost undetectable manner. Thanks to the multiple virtual platforms, communication is currently liquid, due to the appropriation of the new technology and the benefits it shares. Mediatization promotes the divulgation of messages. This is exactly what happened with the reggaeton genre, the same one that conquered the traditional and modern means, exerting a force on the masses and granting themselves power of influence over them. The present investigation shows the relevance of music as a communicational form in the environment of generation z (hereinafter teenagers), which is ascribed to specific musical forms such as the genre of reggaeton.